2019
DOI: 10.2478/auseme-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Study of Powder Particle Size Effect on Microstructural and Geometrical Features of Laser Claddings Using Response Surface Methodology RSM

Abstract: A continuous CO2 laser (10.6 µm wavelength) was adopted to investigate the influence of powder particle sizes on microstructural and morphological characteristics of laser claddings. To study the potential of powder in controlling the incident laser energy, different average particle sizes of Ni-base powder were deposited on an austenitic stainless steel X3CrNi18-10 substrate. The energy value necessary to melt a mass m of powder was calculated. The results indicate that this energy decreases with particle siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Studies have shown the effect of the treatment on the geometric quality of the laser sheath obtained by powder injection [9], [10]. However, the effectiveness of protecting coatings against corrosion remains to be examined.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown the effect of the treatment on the geometric quality of the laser sheath obtained by powder injection [9], [10]. However, the effectiveness of protecting coatings against corrosion remains to be examined.…”
Section: Introductionmentioning
confidence: 99%